Effect of heatwaves on daily hospital admissions in Portugal, 2000–18: an observational study - Alho, Ana Margarida (2024)
Background Climate change has increased the frequency, intensity, and duration of heatwaves, posing a serious threat to public health. Although the link between high temperatures and premature mortality has been extensively studied, the comprehensive quantification of heatwave effects on morbidity remains underexplored. Methods In this observational study, we assessed the relationship between heatwaves and daily hospital admissions at a county level in Portugal. We considered all major diagnostic categories and age groups (<18 years, 18–64 years, and ≥65 years), over a 19-year period from 2000 to 2018, during the extended summer season, defined as May 1, to Sept 30. We did a comprehensive geospatial analysis, integrating over 12 million hospital admission records with heatwave events indexed by the Excess Heat Factor (EHF), covering all 278 mainland counties. We obtained data from the Hospital Morbidity Database and E-OBS daily gridded meteorological data for Europe from 1950 to present derived from in-situ observations. To estimate the effect of heatwaves on hospital admissions, we applied negative binomial regression models at both national and county levels. Findings We found a statistically significant overall increase in daily hospital admissions during heatwave days (incidence rate ratio 1·189 [95% CI 1·179–1·198]; p<0·0001). All age groups were affected, with children younger than 18 years being the most affected (21·7% [20·6–22·7] increase in admissions; p<0·0001), followed by the working-age (19·7% [18·7–20·7]; p<0·0001) and elderly individuals (17·2% [16·2–18·2]; p<0·0001). All 25 major disease diagnostic categories showed significant increases in hospital admissions, particularly burns (34·3% [28·7–40·1]; p<0·0001), multiple significant trauma (26·8% [22·2–31·6]; p<0·0001), and infectious and parasitic diseases (25·4% [23·5–27·3]; p<0·0001). We also found notable increases in endocrine, nutritional, and metabolic diseases (25·1% [23·4–26·8]; p<0·0001), mental diseases and disorders (23·0% [21·1–24·8]; p<0·0001), respiratory diseases (22·4% [21·2–23·6]; p<0·0001), and circulatory system disorders (15·8% [14·7–16·9]; p<0·0001). Interpretation Our results provide statistically significant evidence of the association between heatwaves and increased hospitalisations across all age groups and for all major causes of disease. To our knowledge, this is the first study to estimate the full extent of heatwaves’ impact on hospitalisations using the EHF index over a 19-year period, encompassing an entire country, and spanning 25 disease categories during multiple heatwave events. Our data offer crucial information to guide policy makers in effectively and efficiently allocating resources to address the profound health-care consequences resulting from climate change.